(untitled) (Research, Society and Development, 2021)
The use of amphetamines is considered a public health problem, as they are among the most used drugs worldwide. Its consumption is common among truck drivers to reduce their time on the road quickly arriving at their destination. In drugstores, the consequences reported to pharmacists after the effect of its use are sleep disturbances, irritability, nervous agitation, memory lapses and hypertension, and at that time, pharmaceutical assistance should be provided to advise on the dangers of its use. Show how pharmaceutical assistance can help in caring for the consequences of the use of amphetamines by truck drivers. The materials used were articles published between the years 2016 to 2021, searched on the research platforms: SciELO (Scientific Electronic Library Online) and Google Scholar. The methods used are: systematic literature review, applying the qualitative research method. Studies show that when truck drivers consume amphetamines, the CNS - Central Nervous System takes action and, through mediators, respond with stimuli of dexterity, self-confidence and inhibiting sleep, and drivers take risks on the highways for prolonging their journey without rest and as consequences can cause rebound effects causing accidents involving other people due to oscillating responses in the CNS. The use of amphetamines by truck drivers is one of the main causes of accidents on roads and highways, including fatalities generated by its effects and pharmacists during assistance should advise that the use of these substances can bring considerable health risks, including chronic diseases.